Politeness strategies in business English discourse - Elena B. Kuzhevskaya (Peoples' Friendship University of Russia (RUDN University), 2019)
Conversational strategies are an important element of any modern English language syllabus. Much attention is paid to teaching these strategies in Business English classrooms. A crucial component of conversational strategies in business is politeness strategies. Awareness of linguistic politeness as a strategy of speech behaviour allows interlocutors to maintain a felicitous pattern of communication and prevent conflict. The present research focuses on politeness strategies realised in business English discourse. Within the framework of the study a corpus of cases was subjected to a comparative analysis in the course of which their overall pragmatic effect on the interlocutor was revealed. Considerable attention was paid to the statistical analysis of the distribution of the four strategies of politeness and their respective sub-strategies in English business communication. The study contains comparative statistical data illustrating manifestations of different strategies of politeness in modern Business English and provides a description of the most common cases of their realisation. Raising awareness of politeness strategies and acquiring practical skills can help both the speaker and the listener to understand implied meanings conveyed in different communicative situations and adjust their speech behaviour to achieve the aims of communication, which ensures success in business.